Development of Ecofriendly Snail Shell Particulate-Reinforced Recycled Waste Plastic Composites for Automobile Application - I. O. Oladele; A. A. Adediran; A. D. Akinwekomi; M. H. Adegun; O. O. Olumakinde; O. O. Daramola (The Scientific World Journal)
The increase in demand for thermoplastics as a light-weight material for automobile application and other commercial purposes prompts more research into the available polymer resources. In this research, the possibility of enhancing the performance of recycled waste plastics (RWP) as polymer-based composites was examined. Particulate snail shell was obtained by grounding and sieving snail shells to obtain 53–63 μm passing which was used as reinforcement in the recycled waste plastics. The composites were developed by adding varying proportions of the snail shell particulate (SSP) to RWP using a randomly dispersed process in a hot compression moulding machine maintained at 190°C for 7 min. Selected properties of SSP-reinforced RWP composites were examined. The results showed an appreciable enhancement in the properties of composites developed compared to an unreinforced RWP matrix that serves as control. The ultimate tensile strength was enhanced by about 64%, while Young’s Modulus and impact strength were enhanced by 37% and 29%, respectively. Wear and water repellant potentials were highly enhanced with the addition of 15 wt% of SSP with values of about 52% and 91%, respectively. This revealed that high content of the SSP contributes to the improvement of the strain-hardening potentials of the developed composites. The results showed that this composite material can be suitably adapted for use in the interior of automobiles as door sills or the floor panel.